Artykuł oryginalnyEstimation of cardiovascular complications and death risk in subjects with metabolic syndrome - Kowalski, Jan; Barylski, Marcin; Godala, Małgorzata; Irzmański, Robert; Brocka, Ewa; Pawlicki, Lucjan (Archives of Medical Science, 2006)
Introduction: Coexistence of lipid and carbohydrate disorders with hypertension and obesity increases the risk of ischaemic heart disease and its complications. The recently observed lack of reduction in the incidence of cardiovascular system diseases is thought to be due to the growing epidemic of MS. The aim of the study was to estimate cardiovascular complications and death risk in subjects with MS. Material and methods: The prevention study included 581 subjects (213 males and 368 females): 250 born in 1949, 155 born in 1959 and 176 born in 1969. MS was diagnosed (on the basis of NCEP ATP III) in 104 individuals. Increased risk of cardiovascular complications was determined for pulse pressure (pp) >63 mmHg. Based on the SCORE index (algorithm), 10-year death risk due to cardiovascular complications was estimated taking into account sex, age, smoking, systolic blood pressure and total cholesterol concentration. A value ³5% was accepted as high risk of death within 10 years. Results: Increased risk of cardiovascular complications (pp >63 mmHg) was found in 21 subjects (20.2%) with MS and 34 (7.1%) without MS (p<0.05). High death risk due to cardiovascular complications (within 10 years, ³5%) was diagnosed in 33 (31.7%) subjects with MS and in 38 (8%) without MS (p<0.05). Conclusions: High risk of cardiovascular complications and death occurs statistically more frequently in subjects with MS than in the rest of the population.